NOWATORSKIE ROZWIĄZANIA KODEKSU KARNEGO SKARBOWEGO NA PRZYKŁADZIE POSTĘPOWANIA MANDATOWEGO - Skowronek, Grzegorz (Wydział Prawa i Administracji UAM, 2003)
The legal solutions adapted in the penal and fiscal code concerning proceedings by police penal orders are an innovative regulation in the penal and fiscal matters adapted for the first time in this area of the Polish law. An analysis of the regulations allows to arrive at the conclusion that proceedings by police penal orders can be conducted only in the case of fiscal violations where there occurs no doubt as to the violating party and the circumstances of the act and the act can be classified as punishable with a fine no larger than double the value of the minimum monthly wages. In principle, fines in such proceedings are imposed by the financial investigating organ, and if any legal provisions stipulate so, also by a non-financial investigating organ. The appropriate investigating organ can conduct proceedings by police penal orders only if such proceedings are permissible, i.e. all the necessary particular conditions are met. The provisions of the penal and fiscal code mention two types of penal fines. The first one, cash fine, is issued to the penalized party after a direct payment of the imposed penalty to the investigating organ or its representative. The second type, loan fine is delivered on acknowledgement to the penalized party. A cash penalty can be imposed on individuals temporarily visiting the territory of the Republic of Poland as well as permanent residents of Poland temporarily leaving its territory. The regulations of the penal and fiscal code in the studies scope still, however, raise some doubts. However, one should emphasise that the draft amendment of the penal and fiscal code due to enter into force in the second half of the present year takes into consideration most of the modifications postulated by the doctrine. The author cherishes hope that the presented study results supported by the subject literature will help both practitioners and theoreticians apply and understand the solutions of the penal and fiscal code in the presented scope.
INNOVATIVE SOLUTIONS IN THE PENAL AND FISCAL CODE ON THE EXAMPLE OF PROCEEDINGS BY POLICE PENAL ORDERS